The Quality of Functional Movements and the Back Squat in Amateur and Professional Bodybuilders - VERONIKA ILJINAITĖ; LAIMONAS ŠIUPŠINSKAS; KRISTINA BERŠKIENĖ (International Journal of Sports Physical Therapy)
# Background